The Aspects of Latvian Traditional Culture and Multiculturalism in the Acquiring of Textile Technologies - Urdziņa-Deruma, Māra; Šelvaha, Lolita; Kokina-Lilo, Mārīte (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Under development of globalization, there is an essential question in each field of education regarding balance of traditional Latvian cultural values and multiculturalism. Despite plenty of activities performed in Latvia in the field of multicultural education, in the subject of home economics and technologies the multicultural education has mostly appeared as bilingual education in national minority schools. There are many opportunities in multicultural education and Latvian traditional culture that have not been used in the acquisition of home economics and technologies. The aim of this research is to evaluate the educational opportunities of Latvian traditional culture and multicultural education during the process of mastering textile technologies. In the article conception of Latvian traditional culture and multicultural education is analysed and its determinative aspects are examined. A case study has been performed in order to analyse and evaluate the content of textile study course and the learning process as well as students’ concluding tasks regarding teaching methodology of textile and textile articles made by pupils within the frame of State Olympiad of household, home economics and technologies called “Ethnography”. In all courses designed for the prospective teachers of home economics and technologies as well as household elements of traditional and multicultural education are included. When acquiring traditional culture, textile techniques, forms and elements of composition, teaching of colours and materials, very often comparisons, illustrations and explanations in terms of traditional culture of other nations are used for comprehension of the subject. Specific tasks are made for acquiring culture of Latvia and other nations. Students make copies of fragments of completed articles and learn the technologies of making traditional articles. Several students in their graduation papers have studied the opportunities of acquiring traditional values of Latvian and other nationalities’ cultures in studies of home economics and technologies. The analysis of works completed in the Olympiad „Ethnography” shows that students make varied creative compositions, using ethnographic symbols as source of inspiration, and implement them in various textile techniques. At the end of the article proposals and conclusions regarding development of Latvian traditional culture and multicultural education studies for the prospective teachers of home economics and technologies are drawn. It is necessary to improve the content of home economics and technologies’ subject as well as the methodological approach in order to implement both traditional and multicultural education in schools and high-schools in the studies of the prospective teachers of home economics and technologies.